THE VAPOR OF LEMONGRASS (Cymbopogon nardus) ESSENTIAL OIL FROM THE DIFFUSER AS MOSQUITO REPELLENT AND TRANQUILIZER - Sendy Junedi; Salsa Billa Putri Renanda; Evelin Erlinda Elma Callista; Gabriella Ayu Chintya Velania Nahak (BRIN - Badan Riset dan Inovasi Nasional, 2025)
The COVID-19 pandemic and dengue fever present significant health challenges, especially in tropical regions such as Indonesia. This study aimed to explore the potential of citronella essential oil (Cymbopogon nardus) vapor, delivered via a diffuser, as both a tranquilizer and mosquito repellent. Citronella oil was isolated by water distillation and analyzed through GC-MS and TLC. The tranquilizing effect was evaluated using the Depression Anxiety and Stress Scale (DASS), while the mosquito repellent activity was tested against Aedes aegypti. Results showed that citronella oil contains key compounds such as citronellal, eugenol, cytronellol acetate and geraniol acetate. DASS scores decreased after exposure to citronella oil vapor, indicating its tranquilizing effect. In the mosquito repellent test, citronella oil caused a 68% mortality rate in Aedes aegypti after 60 minutes. These findings suggest that citronella essential oil vapor from diffusers is effective as both a tranquilizer and mosquito repellent.